2021
DOI: 10.3390/audiolres11020015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Electromyographic Assessment of Swallowing in Individuals with Functional Dysphonia Associated with Dysphagia Due to Muscle Tension or Atypical Swallowing

Abstract: Introduction: Over the past few years, attention has been paid to the coexistence of dysphonia with dysphagia, in the context of functional disorders. The aim of this work was to objectify logopaedic examination of dysphonic patients with coexisting swallowing difficulties by surface electromyography. Methods: The material of the work included 58 patients with muscle tension dysphonia (MTD). Each patient underwent otolaryngologic, phoniatric and logopaedic examination. We collected information about medical hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our results suggest that the loss of symmetrical interaction of the bilateral infrahyoid muscles could be another dysphagia biomarker, which agrees with other authors who found that the bilateral muscle discoordination index was significantly greater in dysphagic than in healthy subjects [13]. Krasnodębska et al also reported that patients with atypical swallowing patterns had significantly greater asymmetry of both the masseter and submental muscles [58].…”
Section: Alterations Of Muscle Interactions In Dysphagiasupporting
confidence: 92%
“…Our results suggest that the loss of symmetrical interaction of the bilateral infrahyoid muscles could be another dysphagia biomarker, which agrees with other authors who found that the bilateral muscle discoordination index was significantly greater in dysphagic than in healthy subjects [13]. Krasnodębska et al also reported that patients with atypical swallowing patterns had significantly greater asymmetry of both the masseter and submental muscles [58].…”
Section: Alterations Of Muscle Interactions In Dysphagiasupporting
confidence: 92%
“…The reliability of sEMG recording from perilaryngeal muscles is typically excellent [18]. However, studies using sEMG measures such as root mean square (RMS) and power spectral density (PSD) of single muscles have shown heterogeneous outcomes for assessment of VH, with some studies suggesting differences in sEMG parameters between patients with muscle tension dysphonia and controls, [19], [20] while others are finding no differences at rest or in various phonatory tasks [21]. This heterogeneity is likely because voicing is a complex neuromuscular activity, and activation differences in one or two single muscles are unlikely to capture this complexity.…”
Section: Introductionmentioning
confidence: 99%
“…With 25 items, the DHI investigates the physical, functional, and emotional impacts that OD may have on the patient's life and provides a self-evaluation of OD severity. To date, the DHI has been used to distinguish between different levels of HRQOL in adult OD patients of etiological heterogeneity in crosssectionally designed studies [19][20][21][22][23][24]. Moreover, the DHI was used to assess changes in swallowing self-perception as an outcome measure of treatment efficacy in patients with Parkinson's disease [25,26], cricopharyngeal spasm and pharyngeal pouch [27], post-thyroidectomy dysphagia [28], and Head and Neck Cancer [29].…”
Section: Introductionmentioning
confidence: 99%